Dengue Hemorrhagic Fever (DHF) Education for Residents of Labuh Baru Timur RT 02/08, Payung Sekaki District, Pekanbaru - Zaini, Abdul Kudus; Kumalasari, Cyintia; Muttaqin, Muhammad Zainal (Journal of Community Service and Society Empowerment, 2024)
This community service is conducted in the form of public health initiatives aimed at combating dengue hemorrhagic fever (DHF) in Indonesia. These initiatives are implemented in Labuh Baru Timur Village, RT 02/08, located in Payung Sekaki District, Pekanbaru City, Riau Province. The target beneficiaries of these activities include toddlers, children, adolescent girls, housewives, and the broader community. The primary objective of this community service endeavor is to enhance the knowledge of the targeted partner communities, particularly mothers who are members of POSYANDU (integrated health post), PUSKESMAS (community health centers), doctors, and village midwives, regarding the causes, consequences, and prevention strategies related to dengue hemorrhagic fever (DHF). The methods employed for executing this community service activity involved conducting household visits and organizing discussions on dengue hemorrhagic fever (DHF). Data about participants’ understanding of DHF were collected through pre-test and post-test questionnaires. The anticipated outcome of these efforts is to reduce the incidence of dengue hemorrhagic fever (DHF) and minimize its impact on affected individuals. In instances where residents are diagnosed with DHF and necessitate hospitalization, the objective is to facilitate their prompt and full recovery, thereby enabling them to resume their daily routines, including school attendance.